Mice overexpressing hepcidin suggest ferroportin does not play a major role in Mn homeostasis. Issue 5 (19th March 2019) - Jin, Lian; Frazer, David M.; Lu, Yan; Wilkins, Sarah J.; Ayton, Scott; Bush, Ashley; Anderson, Gregory J.
Abstract : Knockout mice with constitutively low ferroportin show that ferroportin does not make a major contribution to manganese homeostasis in vivo . Abstract : Manganese is an essential metal that is required for a wide range of biological functions. Ferroportin (FPN), the only known cellular exporter of iron, has also been proposed to play a role in manganese export, but this relationship is incompletely understood. To investigate this in more detail in vivo, we examined the relative distributions of manganese and iron in TMPRSS6 deficient mice, which are characterized by constitutively high expression of the iron regulatory hormone hepcidin and, consequently, very low FPN levels in their tissues. Tmprss6 −/− mice showed frank iron deficiency and reduced iron levels in most tissues, consistent with FPN playing an important role in the distribution of this metal, but manganese levels were largely unaffected. Associated studies using intestine-specific FPN knockout mice showed that loss of FPN significantly reduced the dietary absorption of iron, but had no effect on manganese intake. Taken together, our data suggest that FPN does not play a major role in Mn transport in vivo . They do not exclude a minor role for FPN in manganese homeostasis, nor the possibility that the transporter may be relevant at high Mn levels, but at physiological levels of this metal, other transport proteins appear to be more important.